A Comparative Evaluation of the Effect of Photobiomodulation on the Depth of Anaesthesia During Endodontic Treatment of Teeth with Symptomatic Irreversible Pulpitis—A Prospective Clinical Trial - Akshita Balivada; R Vinay Chandra; D Krithika; B Arvind; Mrinalini Jaichander; Priyanka Girish (Journal of Pharmacy and Bioallied Sciences)
Background: Effective pulpal anesthesia is crucial in endodontic practice, particularly in treating symptomatic irreversible pulpitis. This study explores photobiomodulation therapy (PBMT) as a non-invasive adjunct to traditional anesthesia. Aim: To compare the efficiency of diode laser and Er, Cr:YSGG laser in enhancing anesthesia depth during endodontic treatment of teeth with symptomatic irreversible pulpitis. Methods: A total of 45 patients were divided into three groups: placebo (Group 1), diode laser (Group 2), and Er, Cr:YSGG laser (Group 3). Visual Analog Scale (VAS) scores were recorded at three stages: pre-operative, during access opening, and post-operative. Results: Both laser groups demonstrated significantly lower VAS scores compared to the placebo group. The diode laser showed the most significant reduction in pain during the procedure. Conclusion: Photobiomodulation using diode and Er, Cr:YSGG lasers effectively enhances anesthesia depth during endodontic treatment, with diode laser showing superior results.